The Proximity between Hallucination and Delusion Dimensions: An Observational, Analytic, Cross-Sectional, Multicentre Study - Telles-Correia, Diogo (2017)
In psychiatric classifications, hallucinations (mainly auditory hallucinations) are one of the fundamental criteria for establishing a schizophrenia diagnosis or any of the related psychotic disorder's diagnoses. The conceptual proximity between delusions and hallucinations was maintained until the end of the XIX century, with several supporters during the XX century. Their limits were not yet definitely defined in terms of Descriptive Psychopathology, and much less so in terms of biochemical and anatomical models. In this article we aimed to analyse the dimensions of both hallucinations and delusions in a sample of patients with schizophrenia and schizoaffective disorder. We also intend to find the determinants of the main dimensions of hallucinations. One hundred patients with schizophrenia (80) or schizoaffective disorder (20), 64% males, mean age 39.75, from the outpatient and inpatient units of the Psychiatry Department of Hospital de Santa Maria and the Centro Hospitalar Psiquiátrico de Lisboa were assessed by means of the Psychotic Symptom Rating Scales (PSYRATS) and a structured interview. In this study we designed an empirical based model by means of bivariate Spearman's rank correlation coefficient, and multivariate statistics (linear regression and multiple multivariate linear regression), where the main dimensions of hallucinations are determined by the central dimensions of delusions.